The Role of Klotho in Oral and Maxillofacial Diseases: Mechanisms and Research Progress - Shiqi Lin; Bozhao Wang; Jian Li (Biomolecules)
Klotho, an anti-aging protein, has been extensively studied in systemic conditions such as chronic kidney disease and cardiovascular disorders. In recent years, its pivotal protective role and clinical significance in various oral and maxillofacial diseases have been increasingly demonstrated. It has been demonstrated that Klotho regulates oxidative stress, apoptosis, inflammation, and fibrosis via multiple molecular signaling pathways, including Nrf2, NF-κB, PI3K/Akt/FoxO1, insulin/IGF-1, FGF/FGFR, and Wnt/β-catenin. Consequently, these regulatory effects have been observed in conditions such as periodontitis, oral squamous cell carcinoma, malignant salivary gland tumors, oral submucous fibrosis, etc. Moreover, the decreased expression or dysfunctional activity of Klotho is frequently associated with the onset and progression of these diseases. This study provides a comprehensive review of the underlying mechanisms and recent advances in Klotho research within the realm of oral and maxillofacial diseases, offering novel perspectives for future basic and clinical investigations.